2014
DOI: 10.1093/eurheartj/ehu082
|View full text |Cite
|
Sign up to set email alerts
|

Acquired thrombocytopenia after transcatheter aortic valve replacement: clinical correlates and association with outcomes

Abstract: Acquired thrombocytopenia was common after TAVR and was mostly resolved at patient discharge. The severity of thrombocytopenia after TAVR could be used as an excellent, easily obtainable, marker for worse short- and long-term outcomes after the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
100
2
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(116 citation statements)
references
References 30 publications
11
100
2
3
Order By: Relevance
“…Declines in platelet count, diagnosed as thrombocytopenic events, are commonly found in critically ill patients 5, 6. Postoperative thrombocytopenia was associated with worsened outcomes after VRS 7, 8. However, few studies have explored the prognostic value of baseline platelet counts in patients who underwent VRS, especially in the context of RHD.…”
Section: Introductionmentioning
confidence: 99%
“…Declines in platelet count, diagnosed as thrombocytopenic events, are commonly found in critically ill patients 5, 6. Postoperative thrombocytopenia was associated with worsened outcomes after VRS 7, 8. However, few studies have explored the prognostic value of baseline platelet counts in patients who underwent VRS, especially in the context of RHD.…”
Section: Introductionmentioning
confidence: 99%
“…Thrombocytopenia is common after TAVI, occurring in more than one-third of patients to a significant degree, mostly within the first three postoperative days. [34][35][36] The cause of thrombocytopenia after TAVI is currently unknown, and could be a consumptive mechanism at the valve site, hemolysis, or bone marrow suppression. 34) Although it is also unknown whether the hyper-response to clopidogrel is related to thrombocytopenia after TAVI, the potential risk of bleeding should be considered in patients undergoing TAVI.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that TP can be caused by hemodilution, platelet activation, bone marrow suppression, and mechanical destruction [6,7,8]. Post-TAVR TP has been compared with TP after other cardiac interventions and surgery, and study results reveal that TP is more common and severe after TAVR than after percutaneous coronary intervention and balloon aortic valvuloplasty, but similar to after surgical aortic valve replacement [9,10,11,12,13,14]. A 2-center, large-scale study proved that severe TP can lead to poor clinical outcomes, thus highlighting its significance in post-TAVR management [10].…”
Section: Introductionmentioning
confidence: 99%
“…Post-TAVR TP has been compared with TP after other cardiac interventions and surgery, and study results reveal that TP is more common and severe after TAVR than after percutaneous coronary intervention and balloon aortic valvuloplasty, but similar to after surgical aortic valve replacement [9,10,11,12,13,14]. A 2-center, large-scale study proved that severe TP can lead to poor clinical outcomes, thus highlighting its significance in post-TAVR management [10]. Several studies concerning post-TAVR TP have been conducted, but their conclusions about the predictors and clinical outcomes of TP differ.…”
Section: Introductionmentioning
confidence: 99%